Marketing in travel and tourism - Middleton, Victor T. C.; Fyall, Alan; Morgan, Michael (Amsterdam : Elsevier Science, 2009)
Marketing in Travel and Tourism aims to guide and support readers through the complexities of tourism marketing in the 21st Century. It sets out clear explanations of marketing principles and concepts adapted from mainstream services marketing, and goes on to illustrate the range of applications currently practiced in the modern visitor economy. Now in its fourth edition, and reprinted almost every year since 1988, each chapter of the book has been updated to include current evaluations of all the key developments in marketing, especially consumer centric marketing and the now focal role of the Internet in the marketing mix. The chapters on communicating with cutomers have been extensively rewritten to take account of e-marketing and related marketing developments in tourism that are pulled together in a forward looking Epilogue. This fully revised edition includes: full colour interior with pedagogic features such as discussion questions and exercises to encourage further exploration of key areas new material on the role of e-marketing, motivations and consumer behaviour five in-depth international case studies, including Tourism New Zealand and Agra Indian World Heritage Site, along with 17 mini cases to contextualize learning a companion website: www.elsevierdirect.com/9780750686938, packed with extra resources such as Power Point slides and interactive multiple choice questions to aid teaching and learning Marketing in Travel and Tourism provides a truly international and comprehensive guide to marketing in the global travel industry, an indispensable text for all students and lecturers.
Marketing in Travel and Tourism -- Copyright Page -- Contents -- Dedication -- About the principal authors -- Foreword -- Preface -- Acknowledgements -- List of figures -- List of tables -- List of mini-cases -- Part One: The Meaning of Marketing in Travel and Tourism -- Chapter 1. Introducing travel and tourism -- Chapter 2. Introducing marketing: the systematic thought process -- Chapter 3. The special characteristics of travel and tourism marketing -- Chapter 4. The dynamic business environment: factors influencing demand for tourism -- Part Two: Understanding the Consumer and Marketing Mix in Travel and Tourism -- Chapter 5. Understanding the consumer: tourism motivations and buyer behaviour -- Chapter 6. Market segmentation for travel and tourism markets -- Chapter 7. Product formulation in travel and tourism -- Chapter 8. The evolving marketing mix for tourism services -- Part Three: Planning for Marketing Strategy and Short-term Operational Objectives and Campaigns -- Chapter 9. Marketing research in travel and tourism -- Chapter 10. Planning marketing strategy -- Chapter 11. Marketing planning: the process -- Chapter 12. Planning marketing campaigns: budgeting and evaluating marketing performance -- Part Four: Communicating with and Influencing Consumers -- Chapter 13. The growth and role of information and communications technology and the rise of the dominant consumer -- Chapter 14. E-marketing: the effective use of ITC -- Chapter 15. Distribution channels in travel and tourism: creating access -- Chapter 16. Integrating the promotional and communications mix -- Chapter 17. Brochures, print and other non-electronic information -- Part Five: Applying Marketing in the Main Sectors of Travel and Tourism -- Chapter 18. Marketing tourism destinations -- Chapter 19. Marketing accommodation. Chapter 20. Marketing passenger transport -- Chapter 21. Marketing visitor attractions -- Chapter 22. Marketing inclusive tours and product packages -- Part Six: Case Studies of Marketing Practice in Travel and Tourism -- Case 1 Tourism New Zealand -- Case 2 YOTEL -- Case 3 Agra -- Indian World Heritage Site -- Case 4 Travelodge: -- Case 5 Alistair Sawday Guides -- Epilogue: Prospects for travel and tourism marketing -- References and select bibliography -- Index.
Includes bibliographical references and index.
Keywords: TOURISM -- MARKETING